(untitled) - Barlow, Colin (Kuala Lumpur, 1978)
Contents: 1. Introduction; 2. The early years; 3.Growth amidst dificulty; 4. The technologies of production;... .
Keywords: Ngành cao su và thương mại,Rubber industry and trade; Lịch sử,History; Malaysia,Malaysia